Konflik Hukum Antara Ketentuan Hukum Pidana Islam dan Hak-Hak Sipil? (Telaah Konsep HAM dan Implementasi Ratifikasi ICCPR dan CAT di Indonesia) - Alfitri Alfitri (The Constitutional Court of the Republic of Indonesia, 2016)
Can death penalty or corporal punishment be imposed by a state since it is required by the Shariah, but, at the same time, it is against state’s obligation to guarantee civil rights as documented in such international human right laws as ICCPR and CAT? This article is to analyse the so called conflict of law between the requirements of Islamic criminal law and civil rights in Indonesia with particular reference to its implementation in Nanggroe Aceh Darussalam province. There are growing demands of some Muslims to the implementation of hudud in Indonesia and several Qanun Provinsi Nanggroe Aceh Darussalam have been enacted too. According to the proponent of such implementation, this depicts that the state respects its citizens’ belief and culture which is guaranted under the aegis of the right to self determination. However, Indonesia has ratified some international human right laws which require the state to respect the right to life and prohibit torture and cruel, inhuman or degrading punishment. How should the state react? this article argues that an alternative approach which is able to bridge prolonged polemic between universalims and cultural relativisms with regards to the validity of international human rights norms when being implemented to different legal cultures is very much needed. This is important in order to reduce resistence against international human right laws which are important to safeguard civil rights especially when the criminal justice system of a country has not fulfilled the due process of law.